Supporting Situational Awareness on Aviation Pilots - Lopes, Nuno Moura (2022)
Lopes, N. M., Aparicio, M., & Neves, F. T. (2022). Supporting Situational Awareness on Aviation Pilots: Key Insights Affecting the Use of Electronic Flight Bags Devices. In A. Rocha, H. Adeli, G. Dzemyda, & F. Moreira (Eds.), Information Systems and Technologies: WorldCIST 2022 (Vol. 2, pp. 93–101). (Lecture Notes in Networks and Systems; Vol. 469). Springer, Cham. https://doi.org/10.1007/978-3-031-04819-7_10 ----- Funding Information: Aknowledgements. We are gratefully acknowledged financial support from FCT-Fundação para a Ciencia e Tecnologia, I.P., Portugal, national funding through research grant UIDB/04152/2020-Centro de Investigação em Gestão de Informação (MagIC).